SMART SCHOOL MANAGEMENT INTEGRASI DENGAN FINGERPRINT - Leman, Dedi (Riau Journal Of Computer Science, 2020)
The teaching-learning process that is currently running at the vocational school in Medan is still largely conventional in nature, the teacher conveys subject matter, assignments, quizzes, collection assignments in class and each subject are only done a few meetings a week with limited time. Submission of information / announcements, management and services Academic administration and reporting are still done manually so that it is slow and not effective. The purpose of this study is to create a smart school design with a system web-based online learning to overcome various problems faced by Vocational school in Medan (case study at Vocational Tritech Informatics Medan). Smart school will to be blended learning that combines conventional methods or faces with an online learning system towards smart school. The results of this study are the creation online learning system models so that interaction between teachers and students can be done whenever and wherever to improve the quality of education and administrative management academic as well as accelerating the delivery of information to students and parents about students the development and achievements of each student. And use a fingerprint that is directly integrated with the system to be designed. This can support learning in school and creating a culture / learning environment that is effective and efficient and paperless. Design Smart School software uses the waterfall method which includes five stages, namely: (1) identification of user needs; (2) analysis; (3) design; (4) implementation; and (5) testing. Smart school system design uses object-oriented modeling language, UML (Unified Modeling Language).